2005
DOI: 10.1248/bpb.28.1770
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Plasma Concentration of Progesterone by Protease-Sensitive Urinary Pheromones in Female Rats

Abstract: Various gonadal functions of females are controlled by pheromones in many vertebrates. Pheromones have been found in saliva, skin gland secretions, and urine. For example, pheromones in the urine excreted from male and female rats induce various changes in gonadal function and endocrine state, including reflex ovulation in the absence of coitus and mounting, 1) and a reduction in the oestrous cycle of female rats from 5 to 4 d, 2) and oestrous synchrony among female rats housed together.3) The vomeronasal orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Pre-ejaculatory intromissions are also necessary for the successful transport of spermatozoa into the uterine lumen (Chester and Zucker, 1970). However, it has been demonstrated that after exposure to male urine, the female rats present an increased plasma progesterone (Mora and Sánchez-Criado, 2004;Tomioka et al, 2005). Possibly the neonatally handled female rats are less sensitive to male pheromones.…”
Section: Groupsmentioning
confidence: 99%
“…Pre-ejaculatory intromissions are also necessary for the successful transport of spermatozoa into the uterine lumen (Chester and Zucker, 1970). However, it has been demonstrated that after exposure to male urine, the female rats present an increased plasma progesterone (Mora and Sánchez-Criado, 2004;Tomioka et al, 2005). Possibly the neonatally handled female rats are less sensitive to male pheromones.…”
Section: Groupsmentioning
confidence: 99%
“…Male pheromones are known to induce physiological and hormonal changes in the female endocrine and reproductive system ( Rekwot et al 2001 ). For example, male urinary pheromones have been demonstrated to increase plasma-luteinizing hormone and progesterone levels in females ( Tsai et al 1994 ; Tomioka et al 2005 ). The endocrine system has a role in body weight regulation.…”
Section: Discussionmentioning
confidence: 99%